Nigragillin, Nigerazine B and Five Naphtho-γ-pyrones from Aspergillus japonicus Isolated from Hot Desert Soil - Magdy, Wesam; Abdel-Motaal, Fatma F.; El-Zayat, Soad A.; El-Sayed, Magdi A.; Helaly, Soleiman E. (Natural Products Journal, The, 2017)
Background: Microorganisms are highly diverse sources of bioactive natural products. A valuable set of fungi has been encountered in the hot Egyptian desert soils. The aims of this paper were to isolate soil thermophilic fungi and detect their bioactive metabolites. Methods: Direct incorporation method of soil into PDA medium is used for fungal isolation. The metabolic extracts of the isolated fungi were assayed against four bacterial species, Escherichia coli, Staphylococcus aureus, Neisseria lactamica and Bacillus subtilis. Phytochemical methods were used to isolate active compounds from Aspergillus japonicas. Their structures were determined by the interpretation of the NMR data and high resolution mass spectrometry (HRESIMS). Results: The Ethyl acetate extract of Aspergillus japonicus inhibited the growth of Bacillus subtilis, Escherichia coli, Neisseria lactamica and Staphylococcus aureus. Metabolomic investigation of A. japonicus extra-cellular secretion resulted in the isolation of nigragillin (1); and nigerazine B (2); along with five naphtho-γ-pyrones, flavoasperone (3); rubrofusarin B (4); dianhydroaurasperone C (5); fonsecinone A (6); and aurasperone A (7). The antimicrobial activity of the isolated compounds is also described in this paper. Conclusion: This is the first report on those secondary metabolites from A. japonicus as well as the first full NMR assignments of nigerazine B (2). A. japonicas Compounds 1, 3, 4 and 7 exhibited antibacterial activities against B. subtilis, E. coli, N. lactamica, and S. aureus. Aurasperone A (7), and flavasperone (3) were the most active compounds against the tested Gram positive and Gram negative bacteria.a.
Keywords: secondary metabolites